The Role of Innovation and Technology in Enhancing the Competitiveness of the Global Halal Industry - Lailatun Nuroniyah; Nawaliyah Nawaliyah; Mahmudi Ja’far; Moh Aminulloh; Hawa Gazani (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the role of innovation and technology in enhancing the competitiveness of the global halal industry, which is currently growing rapidly in line with the increasing demand for quality halal products that comply with Sharia principles. Using a descriptive qualitative approach, this study examines various literature, policy reports, and industry documents related to the application of technologies such as Artificial Intelligence, the Internet of Things, blockchain, and the digitalization of halal certification. The results show that innovation has a significant contribution to creating added value, increasing production efficiency, and expanding the market share of the halal industry. Technology integration has been proven to strengthen supply chain transparency, accelerate the halal certification process, and increase consumer trust through a more accurate traceability system. Furthermore, digitalization has also driven the transformation of halal MSMEs through the optimization of digital marketing and the utilization of e-commerce platforms. However, the adoption of innovation and technology still faces obstacles such as limited resources, low digital literacy, and a lack of supporting infrastructure, especially among MSMEs. This study concludes that collaboration between the government, certification bodies, academics, and industry players is essential to strengthening a sustainable and globally competitive halal innovation ecosystem.